2011
DOI: 10.1097/jom.0b013e31822cfd4f
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Teaching Occupational Medicine to Medical Students

Abstract: Nonrecognition and mismanagement of work-related diseases is often linked to inadequate medical training. However, undergraduate training in occupational medicine faces many challenges, including lack of student interest and limited curriculum time. The purpose of this article is to present an undergraduate training program developed in one medical school to ensure that all medical students acquire the basic knowledge to recognize work-related health conditions and understand the fundamental principles of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…An additional benefit of the online patient-based scenarios may be to facilitate interest in and acquisition of knowledge and competencies in occupational medicine as implemented in training of medical students. 40 Occupational health physiotherapy as a subspecialty receives limited curriculum time in most undergraduate programs 41 despite the prevalence and cost of work-related injuries in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit of the online patient-based scenarios may be to facilitate interest in and acquisition of knowledge and competencies in occupational medicine as implemented in training of medical students. 40 Occupational health physiotherapy as a subspecialty receives limited curriculum time in most undergraduate programs 41 despite the prevalence and cost of work-related injuries in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study revealed the important roles safety climate and self-efficacy play in shaping NSIs prevention behaviours. Hospitals can improve safety climate by developing strategies to strengthen management commitments to NSIs prevention [48], and provide welldesigned skill-based training to increase physicians' self-efficacy [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…Navon et al [16] used safety role models, safety training programmes, and rewarding employee safety performance to increase safety self-efficacy. As shown in past research [39,41], an effective training programme should include various skill-based learning to strengthen workers' beliefs about their abilities to avoid injuries/accidents safety. These recommendations can be applied to hospital settings to enhance physicians' NSI prevention self-efficacy.…”
Section: Plos Onementioning
confidence: 97%
“…As per International Labour Organization (ILO) estimates, approximately two million workers worldwide die from workrelated injuries and illnesses. 1 Men suffer two-thirds of those deaths with groups of a r t i c l e 3 Universidad Central de Venezuela, Venezuela 4 Health Sciences University of Mongolia, Mongolia 5 Universidad del Rosario, Colombia 6 Federal University of Parana, Brazil 7 Hainan Medical University, China 8 Istanbul University, Cerrahpasa Medical Faculty, Turkey 9 University of Zagreb, Croatia 10 Universidad Austral, Chile 11 University de Los Andes, Chile 12 Maulana Azad Medical College, India 13 Kathmandu Medical College, Nepal 14 Northern Institute of Medical sciences, Pakistan 15 University of Malaya, Malaysia 16 Universidad Rafael Landivar, Guatemala 17 Universidad Catolica del Norte, Chile 18 Usmanu Dan Fodio University, Nigeria 19 Ebonyi State University, Nigeria 20 Universidad Alas Peruanas, Peru 21 Nofer Institute of Occupational Medicine, Poland cancers, circulatory diseases and communicable diseases being the most common, 2 however poor recording and differences in the recording criteria should not be overlooked. Not only the physical and psychosocial effects but also the economic aspect of work-related diseases cannot be disregarded.…”
Section: Introductionmentioning
confidence: 99%
“…6 Non-recognition and mismanagement of work-related diseases is often linked to inadequate medical training. 7 Therefore, not only for furnishing information on OSH, but also for diagnosing, combating and preventing occupational diseases, the knowledge of physicians and paramedical specialists in particular, should be up-todate regarding the potential causal relationship between work and the diseases. 8 Moreover, they should also be familiar with the basic legal aspects of OSH in the industrialized as well as in transition nations.…”
Section: Introductionmentioning
confidence: 99%